2004
DOI: 10.1007/s00192-004-1226-9
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the characteristics and satisfaction degree of the patients using a pessary

Abstract: The objective of this study was to evaluate characteristics, satisfaction degree, and problems of patients using a pessary for pelvic organ prolapse. A total of 104 patients who had been fitted with a pessary and available for follow-up for pelvic organ prolapse management were enrolled. The patients answered questions on general characteristics, indications for pessary use, complications from pessary use, satisfaction degree, and frequency of removal. The results indicated that 76 (73.0%) patients had at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
6
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 24 publications
1
28
6
3
Order By: Relevance
“…Complications were related to pessary shape and material, and duration in situ [21]. Sang et al reported that 76 (73.1%) patients had complications such as bleeding, erosion, or foul odor [11]. Erosions and abnormal vaginal bleeding were the most common complications in our patients, which was consistent with the results reported in previous literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Complications were related to pessary shape and material, and duration in situ [21]. Sang et al reported that 76 (73.1%) patients had complications such as bleeding, erosion, or foul odor [11]. Erosions and abnormal vaginal bleeding were the most common complications in our patients, which was consistent with the results reported in previous literature.…”
Section: Discussionsupporting
confidence: 90%
“…Bai et al investigated 104 patients fitted with pessaries, of whom 19.1% removed their pessaries. Most patients (80.0%) were unable to continue use due to the repeated expulsion of the pessary and uncomfortable fitting [11]. We found difficulty in inserting or removing (19.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal pessaries are well tolerated and improve the symptoms associated with POP [7][8][9][10][11][12][13][14]. However, few studies used validated questionnaires [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was based on previous data that 70-92% with a mean value of 81% of patients was satisfied after pessary use due to improvement of symptoms associated with prolapse [7,8]. A sample size of 60 was calculated with 95% significant level and 10% maximum allowable error.…”
Section: Methodsmentioning
confidence: 99%
“…The TIPI is a new disposable device which can be self-inserted into the vagina on a daily basis. This disposable device offers a potential advantage over existing incontinence pessaries in that traditional pessaries largely remain in place for much prolonged periods and could have the potential to be associated with vaginal erosion [17], foul odors, infections, and irritation [18]. In contrast, the TIPI device during usage was given a mean comfort score of 3.49 on a five-point scale, with 91.2 % of patients maintaining use.…”
Section: Discussionmentioning
confidence: 99%